Procedural Law of Ukraine in the Cossack Era (16th – 18th Centuries) - D. V. Slynko (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The research is devoted to the study of the procedural law of Ukraine in the Cossack era. It is established that the process of law-making on the territory of Ukraine has been ongoing and has a thousand-year tradition. The development of legal norms, including procedural ones, in the Ukrainian lands did not stop even in the periods of absence of the Ukrainian nation-state. This is due to the preservation of customs and traditions of people’s government and self-government in the popular consciousness. It is determined that the Cossack law and its procedural component were a system of customary legal norms which owed their origin to the social phenomenon of the Cossacks. It is noted that the revival of Ukrainian statehood, in turn, contributed to the further development of procedural rules, since the further genesis of procedural law was based on the universals of hetmans and colonels. The structure of the Cossack State was determined by the traditions of people's rule in the organisation and exercise of power. The unique legal innovations in the area of judicial proceedings enshrined in the 1710 Constitution of Pylyp Orlyk are examined. Although these provisions were not practically implemented, they demonstrated a fairly high level of development of Ukraine’s procedural law during this period and revealed to the world the maturity of Ukrainian statehood ideas, according to which the judicial system was viewed as an independent, separate branch of government. Attention is drawn to the continued influence of ecclesiastical customary law on Ukrainian lands during this time. This is due to the fact that, among other factors, the effectiveness of the procedural component of Cossack law largely depended on Orthodoxy, as it served as a normative and value-based measure for Cossack customs and their application. It is noted that the manifestations of procedural law in the Ukrainian lands can be considered the procedural rules which were in force on the territory of Ukraine as a result of the influence of the Polish-Lithuanian Commonwealth, the Moscow State and the procedural component of Magdeburg law.